FAKTOR RESIKO INDIVIDUAL PADA PREEKLAMPSIA PADA RSUP DR M DJAMIL PADANG - Yusrawati, Yusrawati; Machmud, Rizanda (Fakultas Kedokteran Universitas Andalas, 2017)
Preeclampsia is an important issue in obstetrics because it is still a major cause of maternal mortality compared to bleeding and infection. Similarly, the national prevalence, preeclampsia prevalence in West Sumatra is also constantly increasing. Many factors have been identified as risk factors. This study purposed to identify and analyze risk factors of preeclampsia consist of individual factors. This study was an analytical observational study with case-control design, done in Obstetrics and Gynaecology Department of RSUP DR. M. Djamil Padang on January-December 2013 until samples were completed. Samples consist of 70 preeclampsia patients as the treatment group and 70 healthy maternity patients as the control group in RSUP DR. M. Djamil Padang. The results showed there were significant differences between individual risk factors in the preeclampsia group than the control group.Keywords: Individual Risk Factors, Preeclampsia